HUBUNGAN ANTARA KOMPETENSI GURU DAN MINAT BELAJAR SISWA DENGAN TINGKAT PRESTASI BELAJAR SISWA KELAS XI IPS SMA NEGERI 2 SUKOHARJO TAHUN AJARAN 2011/2012 - Yuliarti T.S.U, Ika (ISSN.2252-8407)
ABSTRACT This study aims to determine the relationship between teacher competence and student interest in learning achievement levels of students in class XI IPS 2 Sukoharjo SMA. To achieve these objectives the research carried out by using the media poll involving 156 students of class XI IPS 2 Sukoharjo SMA. In this study the sampling technique used was cluster sampling (sampling berumpun way). Data collection in the study conducted using a questionnaire consisting of questionnaires and tests. A questionnaire was used to measure the variables of teacher competence and student interest, while containing test instrument used to measure student learning outcomes especially sociology subjects. Subsequent to the validation of measuring instruments, items declared killed 1 of 20 grains of teacher competence questionnaire, fall 6 items from the 20 item questionnaire and 20 students' interest in learning about the learning outcomes test results. Data processing was performed using descriptive statistical analysis and product moment correlation and services with the help of a computer program SPSS for windows. Through the analysis of data obtained rX_1Y = 0.090 and ? = 0.295 so that there is a relationship between teacher competence and student achievement SMA XI IPS 2 Sukoharjo less significant relationship exists. Relative contribution (SR) of 6,715% and the effective contribution (SE) ??of 0.625%. rX_2Y = 0.295 and p = 0.001 so that there is a significant relationship between students' interest in learning achievement of class XI IPS SMA Negeri 2 Sukoharjo there was a significant relationship. Relative contribution (SR) 93,285% and the effective contribution (SE) ??of 8,682%. And rX_1 x_2 Y = 0305 and ? = 0.002 so that there is a relationship between teacher competence and student interest in class XI student achievement IPS SMA Negeri 2 Sukoharjo there was a significant relationship. Relative contribution (SR) of 100,000% and the effective contribution (SE) ??of 9,307%. Other variables that are not mentioned in this study may also affect.   Keywords: teacher competency, student interest, academic achievement.